All Days 2011
DOI: 10.2118/140278-ms
|View full text |Cite
|
Sign up to set email alerts
|

Management of Asphaltenes Deposition in a Giant Carbonate Onshore Oil Field, Abu Dhabi, U.A.E.

Abstract: Recently observed production behavior in a maturing carbonate oil reservoir indicated that many production strings were getting plugged with solid scales, requiring tubing clean-out jobs. This is the main reservoir of a supergiant onshore carbonate oil field operated by ADCO since 1973. Some cases proved to be no more than calcium carbonate scaling following water breakthrough and the tubing blockage was successfully treated with acid washing. A number of plugged strings revealed that a non-mineral hard scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Deposition is the consequence of the aggregation of asphaltene particles to a size which can settle down. The aggregation process might be governed by factors such as crude oil SARA composition and asphaltene composition and properties like polarity, dielectric constant, etc. , On the other hand, the amount of asphaltene deposition might depend upon the overall asphaltene weight percent in the crude oil in the dissolved phase. An oil sample having a higher potential of generating asphaltene deposits at faster rates is more risky than an oil sample that produced a lower amount of asphaltene at slower rates.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deposition is the consequence of the aggregation of asphaltene particles to a size which can settle down. The aggregation process might be governed by factors such as crude oil SARA composition and asphaltene composition and properties like polarity, dielectric constant, etc. , On the other hand, the amount of asphaltene deposition might depend upon the overall asphaltene weight percent in the crude oil in the dissolved phase. An oil sample having a higher potential of generating asphaltene deposits at faster rates is more risky than an oil sample that produced a lower amount of asphaltene at slower rates.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It was also reported that asphaltenes collected from the field are more polar than asphaltene extracted from the same crude under laboratory conditions . Lastly, the geological settings, presence of tar mat, and biomarker correlation of the crude oil and the source rock also facilitate the determination of asphaltene stability in oils . However, these methods are still not very common or mature and add difficulty to the interpretations of instability and stability from the obtained results.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 4 shows that the CIIs of both Well A and Well B were comparable or higher than those from other fluids from locations in the Middle East (Kokal 2003;Misra et al 2011;Kabir and Jamauddin 2002;Al-Qattan et al 2012) and Venezuela (Garcia et al 2001) that have experienced asphaltene problems in their production systems.…”
Section: General Remarks On Field 'M'mentioning
confidence: 89%
“…It was observed that the asphaltene precipitation decreased at a high ratio of resin to asphaltene, and the resin polar head coated asphaltene molecules and the nonpolar parts interacted directly with oil [17]. Asphaltenes stability was analyzed by many methods including: the Colloidal Instability Index (CII) [18,19], De Boer's diagram [20], Refractive index [3] and hydrogen to carbon ratio [21]. Asphaltenes Precipitation Envelopes (APE), gravimetric, acoustic resonance, nearinfrared light scattering and filtration were the most common methods for detecting the severity of asphaltenes [20].…”
Section: Introductionmentioning
confidence: 99%
“…Asphaltenes stability was analyzed by many methods including: the Colloidal Instability Index (CII) [18,19], De Boer's diagram [20], Refractive index [3] and hydrogen to carbon ratio [21]. Asphaltenes Precipitation Envelopes (APE), gravimetric, acoustic resonance, nearinfrared light scattering and filtration were the most common methods for detecting the severity of asphaltenes [20]. Akbarzadeh et al [22] performed a study on the flow assurance problem due to asphaltene precipitation.…”
Section: Introductionmentioning
confidence: 99%